Biodiversity and resilience interventions: Analysis of interviews with farmers in France - Kuncz, Adina; Lefeuvre, Nastasia Boul; Dray, Anne; Zhang, Wei (International Food Policy Research Institute, 2022)
This note summarizes the results of interviews with 17 farmers in France to identify the motivations and challenges that impact farmers’ adoption of practices that improve biodiversity. Respondents were identified through the Chamber of Agriculture Nord Pas de Calais and through the farmer network of the team leader with a further snowballing approach to find additional potential participants, and thus were not representative. All interviews were conducted either in-person or on Zoom. This work was part of the Enhancing Biodiversity and Resilience in Crop Production project, which was commissioned by Bayer and implemented in collaboration with ETH Zurich and IFPRI. The project analyzed information that can contribute to guidance on using agricultural practices to improve biodiversity and resilience of farming systems. It focused on intensive maize, wheat, and soy production systems in France, Germany, Brazil, and the United States.